Diagnosis of Appendicitis in Patients with Abnormal Position of the Appendix due to Mobile Caecum. (19th November 2012) - Toprak, Huseyin; Bilgin, Mehmet; Atay, Musa; Kocakoc, Ercan
Abstract : Acute appendicitis is usually diagnosed on the basis of signs, symptoms, clinical history, physical examination, and results of laboratory tests.The position of the appendix can vary considerably, both in relation to the caecum and because of the inconsistent position of the caecum itself, and may cause variable clinical symptoms. We present the CT findings of surgically proven acute appendicitis associated with atypically located caecum in two patients.